The Reframing Business Model Innovation Through Dynamic Capabilities A Two-Decade Global Bibliometric and Network Mapping (2006–2026) - Aida Vitria; Muhammad Zaini (Cita konsultindo, 2026)
This study aims to provide a comprehensive and integrative mapping of the global research landscape on Business Model Innovation (BMI) through the lens of Dynamic Capabilities (DCV) over a two-decade period (2006–2026), addressing the persistent research problem of conceptual fragmentation between these domains. Adopting a bibliometric approach combined with network analysis, the study analyzes 1,137 scientific articles sourced from Scopus and Google Scholar databases, selected using the PRISMA framework to ensure methodological rigor and relevance. Data were processed using VOSviewer to generate network, overlay, density, and co-author collaboration visualizations, enabling the identification of intellectual structures, thematic evolution, and collaboration patterns within the field. The findings reveal that dynamic capabilities function as the central theoretical anchor, supporting the reconceptualization of BMI as a capability-driven and iterative process rather than a static strategic outcome. The literature is dominated by themes related to digital transformation, artificial intelligence, sustainability, and circular economy, indicating a shift toward techno-socio-ecological perspectives in strategic management. However, the results also highlight significant fragmentation, particularly in peripheral themes such as entrepreneurship, innovation ecosystems, and microfoundations, as well as weak collaboration networks among scholars. These findings underscore the novelty of this study in bridging fragmented research streams and advancing a more coherent theoretical integration of BMI and DCV. The study contributes theoretically by positioning DCV as a unifying framework, methodologically by demonstrating the value of multi-visual bibliometric analysis, and practically by emphasizing the importance of capability development for firms navigating digital disruption and sustainability challenges.